1991
DOI: 10.1159/000216274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Recombinant Hirudin

Abstract: Pharmacological profiling of recombinant hirudin (r-hirudin) has shown that this selective tight-binding thrombin inhibitor is a potent, well-tolerated anticoagulant. Clinical pharmacological studies were performed in human volunteers after single and repeated doses of 0.1–0.5 mg/kg. Generally, administration of r-hirudin was tolerated without side effects. Thrombin time and partial thromboplastin time were prolonged dependent on the r-hirudin level in plasma. Platelet counts, fibrinogen level and fibrinolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Because hirudin is said to be highly thrombin-specific and pharmacodynamically inert (22,23), it appears that its protective effect is caused by inhibition of endogenous thrombin. This, in turn, strongly suggests that endogenous thrombin participates in ischemia-induced neurodegeneration in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…Because hirudin is said to be highly thrombin-specific and pharmacodynamically inert (22,23), it appears that its protective effect is caused by inhibition of endogenous thrombin. This, in turn, strongly suggests that endogenous thrombin participates in ischemia-induced neurodegeneration in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The analogous thrombin inhibitor, hirudin, was isolated from the leech Hirudo medicinalis. Hirudin is also a potent (K i 20 fM) and competitive thrombin inhibitor and a purified recombinant version has entered clinical use [38][39][40][41]. Comparative studies with both proteins have concluded that TAP yields an equivalent anticoagulant benefit with a reduced incidence of bleeding side effects [42,43].…”
Section: Possible Points Of Interventionmentioning
confidence: 99%
“…After pharmacotoxicological profiling of rH, we began preclinical and clinicopharmacological investigations in 1988 (82,85, 87,90,92,105). These studies and subsequent ones from other researchers showed that the pharmacological properties of rH are very similar to those of nH.…”
Section: Preclinical Studiesmentioning
confidence: 99%